A REPORT ON ANOMALIES OF DIGASTRIC MUSCLE - Holibková, Alžběta; Machálek, Libor (Biomedical papers, 1999)
Dedicated to the memory of doc. MUDr. et RNDr. Milan Èerný, CSc.The anterior belly of the digastric muscle varies greatly in shape and size. In this report, two cases of anomaliesin the digastric muscle found in necropsy material belonging to the Institute of Anatomy are described. In the firstcase, we found a bilateral anomaly - a lateral widening of the muscle belly as an adaptation; this was shown byseparation of the anterior muscle belly of digastric muscle into a medial and lateral head. The latter of whichpassing through the intermediate tendon and fixing partially on the hyoid bone. In the second case, a bilateralasymmetrical anomaly of the anterior belly was described. This involved the separation of the anterior belly intomedial and lateral parts and the occurrence of accessory bundles; these bundles run from the left part of themandible to the intermediate tendon of the right side of digastric muscle and to the hyoid bone.
Keywords: Neck muscles / Digastric muscle / Abnormalities